Quantum dot-decorated silicon nanowires as efficient photoelectrodes for photoelectrochemical hydrogen generation - Devarapalli, Rami Reddy; Kamaja, Chaitanya Krishna; Shelke, Manjusha V. (Journal of Materials Chemistry A, 2014)
Quantum dot-decorated wide band gap semiconductors, such as TiO2, ZnO, SnO2, etc., which have electron mobilities of less than 200 cm(2) V-1 S-1 have been well studied as the photoelectrodes for photovoltaics and photoelectrochemical water splitting. Herein, we report CdSe quantum dot decorated-silicon nanowires (SiNWs) as photoelectrodes for photoelectrochemical water splitting. SiNWs have a comparatively higher electron mobility than metal oxides. A photocurrent density of around 6.1 mA cm(-2) was obtained for the CdSe/SiNWs photoelectrode, which is nearly five times higher than that for SiNWs alone and which also shows a good transient photocurrent response. The band energy level alignment was also studied between Si and CdSe by observing the corresponding flat band potentials from a Mott-Schottky analysis.

RuO2 center dot nH(2)O nanoparticles anchored on carbon nano-onions: an efficient electrode for solid state flexible electrochemical supercapacitor - Muniraj, Vedi Kuyil Azhagan; Kamaja, Chaitanya Krishna; Shelke, Manjusha V. (ACS Sustainable Chemistry & Engineering, 2016)
A flexible solid state electrochemical capacitor based on hydrous RuO2 nanoparticles, supported onto the nonporous and highly accessible ion adsorptive carbon nano onions (CNOs), is fabricated in a novel process of modifying a conducting carbon paper to a flexible conducting substrate, separated with a poly(vinyl alcohol)/H2SO4 gel electrolyte. The sol-gel technique tends to form homogeneously dispersed RuO2 nanoparticles with the average size of similar to 2.3 nm on the positive surface curvatures of multilayer fullerene (CNOs), which helps the high diffusivity of ions in both the aqueous and solid state gel electrolytes. The flexible substrate worked excellently as an electrical conductor as well as a stable mechanical support. This solid state flexible energy storage device showed a maximum energy density of 10.62 Whkg(-1) and a maximum power density of 4.456 kWkg(-1) for the hydrous RuO2/CNOs nanocomposite with 94.47% cycling stability even after 4000 cycles.
Keywords: Carbon nano-onions; Electrochemical capacitor; Flexible conducting substrate; Flexible energy storage device; Hydrous ruthenium oxide nanoparticles

Sunlight assisted degradation of dye molecules and reduction of toxic Cr(VI) in aqueous medium using magnetically recoverable Fe3O4/reduced graphene oxide nanocomposite - Boruah, Purna K.; Borthakur, Priyakshree; Darabdhara, Gitashree; Kamaja, Chaitanya Krishna; Karbhal, Indrapal; Shelke, Manjusha V.; Phukan, Pallabi; Saikia, Dulen; Das, Manash R. (RSC Advances, 2016)
In view of the significant impact of magnetically recoverable catalysts in photocatalytic applications, Fe3O4/reduced graphene oxide (rGO) nanocomposite photocatalyst was synthesized by adopting an eco-friendly solution chemistry approach and has been characterized by high resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy and photoluminescence (PL) spectroscopy. Fe3O4/rGO nanocomposite is efficiently utilized towards photocatalytic degradation of carcinogenic and mutagenic cationic as well as anionic dye molecules namely methyl green (MG), methyl blue (MB) and rhodamine B (RhB) under direct sunlight irradiation. The Fe3O4/rGO nanocomposite also demonstrated excellent photocatalytic reduction of aqueous Cr(VI) solution to nontoxic aqueous Cr(III) solution of more than 96% within 25 min under sunlight irradiation. Moreover, reusability of the magnetically recovered photocatalyst was studied efficiently up to 10 cycles in the degradation process. The catalyst was also characterized after the degradation of the dye molecule and the particle size of the Fe3O4 nanoparticles on the rGO sheets remained unchanged. The present investigation focuses on the importance of the use of Fe3O4/rGO nanocomposite towards photocatalytic degradation of waste water containing organic dye pollutants and toxic Cr(VI), as an easily recoverable and reusable photocatalyst with potential for many environmental remediation applications.

Synthesis of novel Cu2S nanohusks as high performance counter electrode for CdS/CdSe sensitized solar cell - Kamaja, Chaitanya Krishna; Devarapalli, Rami Reddy; Dave, Yasha; Debgupta, Joyashish; Shelke, Manjusha V. (Journal of Power Sources, 2016)
An important component of quantum dot sensitized solar cells (QDSSC) is the counter electrode which mediates the regeneration of oxidized quantum dots by reducing the polysulphide electrolyte. However, design and synthesis of an efficient counter electrode material is a challenging task. Herein, we report the synthesis of a unique Cu2S nanohusks directly on FTO coated glass substrates by electrodeposition and used as a counter electrode in QDSSC. When these electrodes are used for the reduction of polysulfide electrolyte in QDSSC, they exhibit higher catalytic activity and photovoltaic performance as compared to the Platinum counter electrode. The power conversion efficiency of about 4.68% has been achieved by optimizing the deposition time of Cu2S. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: counter electrode; Cu2S electrodeposition; Cu2S nanohusks; Quantum dot-sensitized solar cell

Co-catalytic metal oxide nanoparticles decorated silicon/hematite core shell nanowire arrays as efficient photo electrodes for water splitting - Devarapalli, Rami Reddy; Kamaja, Chaitanya Krishna; Shelke, Manjusha V. (ChemistrySelect, 2017)
By looking global energy demands, development of highly efficient stable semiconductor photoelectrodes for photoelectrochemical (PEC) water splitting is highly desirable. Herein, we have fabricated co-catalytic nanoparticles decorated Silicon nanowire (SiNWs)/Hematite(Fe2O3) core sell structures as photo anodes and studied the PEC water oxidation properties. As, Fe2O3 possess weak oxidation kinetics, decoration of NiO and Co3O4 nanoparticles on SiNW/Fe2O3 by hydrothermal method, which acts as co-catalysts to improves the water oxidation reactions. It was found that decoration of Co3O4 nanoparticles enhances the photocurrent up to 2.6 times, whereas for NiO nanoparticles improvement is of 1.5 times when compared to the undecorated electrodes. Along with enhancement of photocurrents, it also shows shift of onset potentials. The effect of the co-catalytic nanoparticles on the enhancement of photocurrent and charge transfer resistance at the interface of electrode-electrolyte have been studied by electrochemical impedance spectroscopy. Further, flat band potentials of the photo electrodes have been measured by using Mott-schottky analysis.
Keywords: Co-catalysts; photo anodes; Photoelectrochemical cell; silicon nanowires; water splitting

One-step synthesis of a MoS2-CuS composite with high electrochemical activity as an effective counter electrode for CdS/CdSe sensitized solar cells - Kamaja, Chaitanya Krishna; Devarapalli, Rami Reddy; Shelke, Manjusha V. (Chemelectrochem, 2017)
Inorganic nanostructured composite materials involving metal sulfides are increasingly important in electrochemical applications like solar cells. In this research, we have developed a one-step in situ solvothermal method to synthesize a MoS2-CuS composite. MoS2 sheets increase electron-transfer ability, assisting the improvement in catalytic activity of the MoS2-CuS counter electrode. The charge-transfer resistance derived from impedance spectroscopy for the MoS2-CuS composite counter electrode at the electrode/electrolyte interface is very low, as compared to MoS2, mostly owing to the increased number of active catalytic sites for the reduction of polysulfide electrolyte. The Tafel polarization plot shows excellent electrocatalytic activity of the MoS2-CuS composite towards polysulfide electrolyte. Finally, the CdS/CdSe sensitized solar cell achieves a power conversion efficiency of about 5% upon optimization of the MoS2-CuS composition.